Agent of Change, Health Education Related to Decision Making and Independence of Families In Health Prevention of COVID-19 - lindawati; Ani Fadmawaty; Wasludin (Jurnal Obstretika Scientia, 2025)
Covid-19 has become endemic, and it is crucial for families to be able to maintain health throughout this time. This includes being able to recognize infection signs or a family member's risk of contracting the virus and making the best medical options when a family member contracts Covid-19. When information, especially anything new, comes from someone close to them, individuals typically react quickly to it because they can observe the behavior and effect of the person delivering it. Methods: : This study uses a quasi-experimental design. The study focused on 150 families that served as change agents and gave health education to the families that had received it. Pre- and post-questionnaires on knowledge, community decision-making ability, and family independence will be used to gauge the effectiveness of the change agent. The nonparametric Wilcoxon test or t-test will be used for this purpose. Results: p value of 0.000 is assigned to the knowledge variable, the family's decision-making capacity, and the family's independence. Conclusions: These findings suggest that the agent of change has an impact on raising awareness, decision-making skills, and family independence in the healthcare.